Morphological and Taxonomic Analysis of the Quercus faginea and Quercus canariensis (Fagaceae) Complexes in Algeria - Ameur Bouandas; Latifa Belhoucine-Guezouli; Francesc Oliva; Bechir Suheil Gaouar Semir; Khedidja Bendjebbar; Francisco M. Vázquez Pardo; Juli Pujade-Villar (International Journal of Plant Biology, 2024)
The valid deciduous Quercus L. species from North Africa have been largely discussed by many authors. The current species remain yet uncertain. In this study, we compare several populations of presumably Q. canariensis Willd. and Q. faginea Lam. from Algeria with pure populations of these species from the northeast of the Iberian Peninsula. Different morphological characters from leaves have been analyzed. Principal components analysis and a canonical analysis of principal coordinates have been used to observe the relationship between samples, groups and the seven quantitative variables. Distances among centroids have been reported and a SIMPER procedure has also been executed to better explain the different variability within and between groups. PERMANOVA has been applied to test for significant differences between the groups. For the trichomes study, ANOVA models have been used. From our analysis, we conclude that in Algeria, we have a single Q. canariensis Willd. population, different from the Iberian population we examined. It probably corresponds morphologically to Q. mirbeckii Durieu, currently considered a synonymy of Q. canariensis Willd., and for the “Q. faginea” group we have two Algerian populations: Q. faginea Lam. subsp. faginea, found in the northeast Iberian Peninsula, and Q. tlemcenensis (A.DC.) Maire and Weiller ex Greuter and Burdet. Previous results from other authors have also been discussed.